Judging Q and Saving Jesus Q's Contribution to the Wisdom-Apocalypticism Debate in Historical Jesus Studies - Howes, Llewellyn (AOSIS, 2015)
The monograph Judging Q and Saving Jesus is characterised by careful textual analysis, showing a piercing critical eye in its impressive engagement with the secondary literature, and sharp and insightful critique. The target audience are specialists in the field of research on the Sayings Source Q (the hypothetical source of certain sayings of Jesus common to Matthew and Luke), historical Jesus, and early Christian theology. The book takes the stance that the hypothetical document Q can be reconstructed with sufficient precision and that this enables biblical scholars to study with confidence its genre and its thematic and ideological profile. The genre issue is central to the book overall structure and the alternative proposals are discussed at length and with sophistication. The author's inference is that Q's macrogenre is sapiential with occasional insertions of apocalyptic microstructures and motifs. This finding embodies progress in Historical Jesus studies.